Aplikasi Perhitungan PPH 21 Dan PPH 26 Karyawan Berbasis Web - Yulia Yulia; Novita Ganiar Anggraini; Lisnawanty Lisnawanty (LPPM Universitas Bina Sarana Informatika, 2020)
Income Tax PPh 21/26 is a tax on I ncome in the form of salaries, wages, honoraria, allowances, and other payments in whatever name and form in connection with work or services. There are also many taxpayers who do not understand how to calculate Income Tax 21/26 on the income they get from their work. therefore, the public must further increase self-awareness to pay taxes and report annual tax returns and knowledge of how to calculate income tax is also useful for taxpayers in the tax reporting process. The purpose of this research is to know and analyze the procedure for calculating the PPh 21/26 employee's income tax calculation system and designing and building an application for calculating the PPh 21/26 employee's income tax. With the application for calculating employee income tax article 21/26, it will make it easier for employees to make tax payment transactions. In the PPh 21/26 Calculation Application the system displays tax payment data, employee data and user data. In making it, the author uses the Codeigniter Framework application with the hypertext preprocessor (PHP) programming language. This program also uses several supporting software in making the Web such as Xampp as a local server, Google Chrome as a Web browser and Mysql as a database server